Preparation of Dense Biphasic Calcium Phosphate Ceramics using Eggshell Derived Nanopowders - Iis, Sopyan; S.A. , Mohamad; S. F., Adlina (Trans Tech Publications Ltd., Switzerland, 2012)
Biphasic calcium phosphate (BCP) nanopowders were synthesized via hydrothermal method using eggshell as the calcium source. The obtained BCP nanopowders were then compacted at various pressure into circular disc shape and sintered pressureless in air at various sintering temperatures. X-ray diffraction analysis of nanopowders revealed the existences of hydroxyapatite (HA) as the main phase, with β-tricalcium phosphate (β-TCP) and calcium pyrophosphate (CPP) as the second phases. Scanning electron microscopy was done to examine the morphology of dense BCP bodies. The effects of sintering temperature and compaction condition on mechanical properties of dense bodies were investigated in terms of compressive strength and Vickers hardness.